Shaping Human Resource Resilience through Failure, Support, and Future Orientation - Bintoro Ariyanto; Derah Sudjaniah; Rita Yuni Mulyanti; Albiansyah Albiansyah (Goodwood Publishing, 2026)
Purpose: This study examines how failure experiences, environmental support, and future orientation influence individual resilience through meaning-making. It also tests the moderating role of growth mindset in strengthening this relationship. Research Methodology: A quantitative cross-sectional survey was conducted with 385 productive-age individuals outside formal organizations. Data were collected using validated scales and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Direct, mediation, and moderation effects were tested using bootstrapping procedures. Results: Failure experiences, environmental support, and future orientation positively affect resilience both directly and indirectly through meaning-making. Meaning-making acts as a key mechanism that transforms experiences and support into psychological strength. Growth mindset strengthens the relationship between meaning-making and resilience. Individuals with stronger growth-oriented beliefs demonstrate higher resilience when they construct meaningful interpretations of their experiences. The model shows strong explanatory power in predicting resilience. Conclusions: Resilience is influenced not only by challenges and support but also by the ability to construct meaning from experiences, with growth mindset amplifying this process. Limitations: The cross-sectional design and reliance on self-reported data limit causal interpretation and generalizability across different contexts. Contributions: This study proposes a moderated mediation framework that highlights meaning-making and growth mindset as central mechanisms in resilience development and provides practical insights for resilience-building interventions.